Malocclusion: A Comprehensive Overview - Mohammed Daifallah Almutairi,; Nadiah Abdulwasea Asrar,; Ahmed Aljamaan,; Alharith Hani Sagga,; Saleh Abdulaziz Aldubayyan,; Fatimah suliman Alshehri,; Salha Mohammed Madkhali,; Abdullah alhammad,; Fahad Abdulaziz Ali Alhajri,; Majdah Salem Al hejali,; Ghada Alshahrani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Malocclusion, the misalignment of teeth or incorrect relationship between the upper and lower dental arches, is a prevalent condition with far-reaching consequences beyond aesthetics. This comprehensive paper explores the multifaceted nature of malocclusions, delving into their etiology, classification, diagnosis, treatment modalities, potential complications, and future directions. The etiology of malocclusions involves a complex interplay of genetic and environmental factors, influencing the development and positioning of dental and craniofacial structures. Diagnosis relies on a thorough clinical examination, radiographic imaging, and the utilization of advanced techniques like cone-beam computed tomography (CBCT). Treatment modalities encompass a range of orthodontic appliances, dental procedures, and, in severe cases, orthognathic surgery. Potential complications of untreated malocclusions include periodontal problems, functional issues, dental problems, and psychosocial impacts. Ongoing research and technological advancements are shaping the future of malocclusion management, with emerging trends such as digital orthodontics, clear aligner therapy, accelerated tooth movement techniques, and personalized treatment approaches. By understanding the complexities of malocclusions and embracing interdisciplinary collaboration, orthodontists and dental professionals can provide comprehensive and effective care, improving patient outcomes and enhancing overall well-being.